Data set. Type I error and power of the F-statistic, and Greenhouse-Geisser and Huyhn-Feldt adjusted F-tests in one-way repeated measures designs under violations of normality and sphericity. - Blanca-Mena, María José; Alarcón-Postigo, Rafael; Arnau, Jaume; García-Castro, F. Javier; Bono Cabré, Roser (Universidad de Málaga, 2025)
Tables correspond to the performance of the F-statistic, and Greenhouse-Geisser (F-GG) and Huyhn-Feldt adjusted F-tests (F-HF) in terms of Type I error and power in one-way repeated measures designs under violation of normality and sphericity. Values of epsilon are fixed according to the Greenhouse-Geisser procedure. The number of repeated measures (3, 4, and 6), sample size (from 10 to 300), non-normal distribution, and epsilon value (from the lower to its upper limit) were manipulated.
Keywords: Psicología - Metodología; Análisis de varianza; Montecarlo, Método de; Sphericity; Normality; Greenhouse-Geisser adjustment; Huynh-Feldt adjustmen